Are International Food Price Spikes the Source of Egypt's High Inflation? - Al-Shawarby, Sherine; Selim, Hoda (World Bank, Washington, DC, 2012)
This paper examines whether domestic inflation spikes in Egypt during 2001-2011 were primarily the result of external food price shocks. To estimate the pass-through of international food price inflation to domestic price inflation, two different methodologies are used: a two-step regression model estimates the pass-through in the long run, and a vector autoregression model provides the short-run estimates. The empirical evidence confirms that pass-through is high in the short term, but not in the long run. More precisely, the results show that (i) long-run pass-through to domestic food inflation is relatively low, lying between 13 and 16 percent, while the long-term spill-over from domestic food inflation to core inflation is moderate, lying around 60 percent; (ii) in the short term, pass-through is relatively high, estimated around 29 percent after 6 months and around two-thirds after a year, but the spill-over effect to core inflation is limited; (iii) international food price shocks explain only a small portion of domestic inflation shocks in both the short and long terms; and (iv) international price inflation has asymmetric effects on domestic prices.